Mobile Learning Research: the Focus for Policy-Makers - John Traxler (Commonwealth of Learning, 2016)
Mobile learning has moved in the last decade from being a small, scattered research interest to being viewed by many international agencies as a way of delivering their humanitarian missions to the developing contexts of the global South.